Enhancing bonding behavior between carbon fiber-reinforced polymer plates and concrete using carbon nanotube reinforced epoxy composites. (December 2022) - Jongvivatsakul, Pitcha; Thongchom, Chanachai; Mathuros, Amaras; Prasertsri, Tosporn; Adamu, Musa; Orasutthikul, Shanya; Lenwari, Akhrawat; Charainpanitkul, Tawatchai
Abstract: Externally bonded carbon fiber reinforced polymer (CFRP) composites have been widely used as repairing or strengthening materials for deteriorated reinforced concrete (RC) structures. This study discusses whether carbon nanotube (CNT) can be used as an additive to enhance bonding strength between concrete and CFRP. In this study, two CNT types: single walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), were mixed with two different types of epoxies. CNTs were added at 0.25%, 0.5%, and 1.00% by weight of epoxy to obtain the optimal performance. Single-shear test were conducted to investigate bonding behavior including bond strength, ultimate slip, effective bond length, bond stress-slip relationship, interfacial fracture energy, and crack formation between CFRP plate and concrete. The results showed that epoxy modified by 0.5% SWCNTs and 1.0% MWCNTs by weight of epoxy enhance the ultimate load and slip, bond strength, and interfacial fracture energy when compared to plain epoxy. However, high density epoxy modified with SWCNTs/MWCNTs showed diminished bonding properties.